Unravelling the functional development of vertebrate pathways controlling gaze - Barandela, Marta; Núñez-González, Carmen; Suzuki, Daichi G.; Jiménez-López, Cecilia; Pombal, Manuel A.; Pérez-Fernández, Juan (Frontiers in Cell and Developmental Biology, 2023)
Animals constantly redirect their gaze away or towards relevant targets and, besides these goaloriented responses, stabilizing movements clamp the visual scene avoiding image blurring. The vestibulo-ocular (VOR) and the optokinetic reflexes are the main contributors to gaze stabilization, whereas the optic tectum integrates multisensory information and generates orienting/evasive gaze movements in all vertebrates. Lampreys show a unique stepwise development of the visual system whose understanding provides important insights into the evolution and development of vertebrate vision. Although the developmental emergence of the visual components, and the retinofugal pathways have been described, the functional development of the visual system and the development of the downstream pathways controlling gaze are still unknown. Here, we show that VOR followed by light-evoked eye movements are the first to appear already in larvae, despite their burrowed lifestyle. However, the circuits controlling goal-oriented responses emerge later, in larvae in nonparasitic lampreys but during late metamorphosis in parasitic lampreys. The appearance of stabilizing responses earlier than goal-oriented in the lamprey development shows a stepwise transition from simpler to more complex visual systems, offering a unique opportunity to isolate the functioning of their underlying circuits.